Mediação da informação e feminismo negro: uma análise de dissertações e teses dos Programas de Pós-Graduação em Ciência da Informação brasileiros - Moura, Ana Patrícia Silva (2025)
The research originated from a master's dissertation and aims to identify, from the theoretical perspective of information mediation, the dissertations and theses linked to Brazilian Postgraduate Programs in Information Science (PPGCI) that address the theme of black women and black feminism, highlighting the subversion and confrontation of racism and sexism. Methodologically, this is a documentary, descriptive research with an exploratory phase and a quantitative-qualitative approach. The corpus was composed of 17 academic PPGCIs, of which 8 have dissertations and theses focused on black feminism published in institutional repositories between 2010 and 2023. In the study sample, there are 7 dissertations and 4 theses written by women. The results indicate that the mediation of informational content produced in dissertations and theses disseminates knowledge of rights, making visible social inequalities of race and gender, corroborating the development of public policies aimed at the social emancipation of black women. It is concluded that it is essential to make visible the productions related to black women and feminisms to subvert the invisibilization of the places of epistemic marginalization allocated to black women.